اللجنة الوطنية للقانون الدولي الانساني ودورها في دعم ادماج ونشر القانون الدولي الانساني في العراق - جعفر, محمود خليل (Journal of Legal Sciences, 2017)
The National Committee of international humanitarian law and its role in supporting the integration and deployment of international humanitarian law in IraqThere are a number of bodies that could help national authorities to better implement IHL. Internally, States may decide to create interministerial working groups, often called committees for the implementation of IHL or national humanitarian law committees, the purpose of which is to advise and assist the government in implementing and spreading knowledge of IHL. Outside the State structures, international organizations and civil society in general may also play an important role through the exchange of expertise and cooperation. Key players in this. Regard are  the National Red Cross and Red  Crescent  Societies